Técnicas cognitivo-conductual de entrenamiento en habilidades sociales para disminuir el comportamiento agresivo de las y los adolescentes del segundo año de bachillerato paralelo “C” de la unidad educativa anexa a la Universidad Nacional de Loja, periodo 2013-2014 - Jiménez Maldonado, José Andrés (2015)
Theresearch consisted to apply the techniques cognitivebehavioralsocial skills training to reduce aggressive behavior of the adolescents of second year of baccalaureate “C” of the Unit Educational attached to the University National of Loja; is a study descriptive, of court cross, with a design quasi-experimental, in a sample of 30 students. Was used methods as: inductive-deductive, synthetic, analytic, historic and logic; also the method comprehensive, diagnostic, of elaboration and application of models and valuation of the effectiveness of the alternative. Was used the survey and the test AQ of Buss and Perry. Results of diagnostic: the 46,67% manifest anger daily and the 80% respond negatively to frustration; in the pre-test: the 30% express physical aggression at high levels and in the post-test: decreases to a 13,33%. The proposal of educational intervention reached a correlation positive come down r(x .y) = 0.35. Conclusions: exist manifestations of behaviors physicalaggressive, verbal, anger, hostility; the intervention influenced of way positive come down in the area of physicalaggressive.